Prevalence and determinants of overweight and obesity among school-aged children and adolescents - Guy Ikambo Wanghi; Leslie Leytle; Zakayi Pius Kabututu; Augustin Rudahaba Buhendwa; Kiswaya Ernest Sumaili (International Journal of Public Health Science (IJPHS), 2020)
Obesity is a significant public health crisis affecting millions of children globally. The objective of this study was to identify the prevalence and associated factors of overweight/obesity among school children in Kinshasa, Democratic Republic of Congo (DRC). This was a descriptive cross-sectional study among school children and adolescents (n= 1442) from Kinshasa selected using multistage sampling method. A structured questionnaire was used to collect behavioral data. The WHO AnthroPlus was used to calculate BMI (body mass index). SPSS version 21 was used for data analysis. Potential covariates were examined using chi-square tests followed by multivariate logistic regression analyzes The study found that out of 1442 students, 72% of the sample was at a healthy weight, 15% were underweight and nearly 13% were overweight or obese. The prevalence of overweight and obesity was higher in girls as compared with boys. The results of multivariate logistic regressions showed that the gender of children, category of age, percent body fat, eating fruits and vegetables, and physical activity levels were significantly associated with childhood overweight/obesity. One in eight children and adolescents (12.8%) aged 6 to 18 years in Kinshasa going to primary and secondary schools were either overweight or obese.